(untitled) (Scientific journal of the Fergana State University, 2024)
This article covers the role of education and its functions in perspective in shaping the ideals of gastronomy in youth thought. Through the formation of ideals of military heroism in youth thought, it consists in the formation of such important characteristics as activity in the future cadres in types of civil service associated with the military sphere, loyalty to the Constitution and military duty in a peaceful and military context, and high responsibility and responsibility for the fate of their country and people in them.